Developing a circular strategies framework for manufacturing companies to support circular economy-oriented innovation. (20th December 2019) - Blomsma, Fenna; Pieroni, Marina; Kravchenko, Mariia; Pigosso, Daniela C.A.; Hildenbrand, Jutta; Kristinsdottir, Anna Rùna; Kristoffersen, Eivind; Shahbazi, Sasha; Nielsen, Kjartan Due; Jönbrink, Anna-Karin; Li, Jingyue; Wiik, Carina; et al.
Abstract: This paper puts forward the Circular Strategies Scanner: a framework that introduces a taxonomy of circular strategies developed for use by manufacturing companies engaging in circular economy (CE) oriented innovation. Currently, a range of frameworks exists that propose a vision for how to operate in a CE, by identifying and organising relevant circular strategies. However, these frameworks have a limited applicability for specific business types, in particular manufacturing, and are unsuitable for use in CE oriented innovation, due to a lacking ability to support innovation processes through: 1) creating a comprehensive understanding of circular strategies, 2) mapping strategies currently applied and 3) finding opportunities for improved circularity across a range of business processes. This paper addresses these shortcomings by proposing a circular strategies framework for the manufacturing context, titled the Circular Strategies Scanner, which provides a comprehensive set of definitions of circular strategies and directly supports the early stages of CE oriented innovation. With this, the paper contributes to the body of work that develops CE transition methodology.